Developing a University–School District Partnership: Researcher–District Administrator Collaboration for a Special Education Initiative - Dyson, Lily (Canadian Journal of Education/Revue canadienne de l’éducation, 1999)
This case study examined the development of a university–school district partnership designed to support a special education initiative with 156 students of middle socio- economic backgrounds in Grades 4 to 7 using critical-sampling, single-case, and docu- mentation methods. It identified four essential elements of researcher–district administrator collaboration: a developmental process led by the partners’ mutual goals and a gradual building of support for the project, a communication protocol dominated by profession- alism and parity, a collaborative structure marked by complementary relationships and accountability between the partners, and outcomes benefitting all stakeholders (teachers, students, and researcher). The most important outcome was students’ increased under- standing of disabilities and empathy with persons with disabilities. The author proposes a conceptual framework for developing university-school partnerships and makes recom- mendations for future practice and research. Cette étude porte sur l’élaboration d’un partenariat entre l’université et une circonscription scolaire en vue d’un projet d’éducation pour des enfants atteints de diverses déficiences. L’auteure identife certains éléments essentiels d’une collaboration entre le chercheur et l’administrateur de la circonscription, soit : (a) un processus d’élaboration axé sur les objectifs mutuels des partenaires et l’établissement progressif d’un appui au projet, (b) un protocole de communication accordant la priorité au professionnalisme et à la parité entre les partenaires, (c) une structure de collaboration caractérisée par des relations de com- plémentarité et une responsabilisation de tous les partenaires et (d) des résultats dont tous les intéressés puissent bénéficier. L’auteure propose un cadre conceptuel pour l’élabora- tion de partenariats entre l’université et l’école ainsi que des recommandations pour des expériences et recherches futures.